Effect of n-3 PUFA rich fish oil supplementation on the reproductive performance of seasonally acyclic goats - YADAV, DUSHYANT; SINGH, AMIT KUMAR; TEELI, AAMIR SALAM; KUMAR, PUNEETH; KUMAR, BRIJESH; SINGH, SANJAY KUMAR; KUMAR, HARENDRA; SINGH, GYANENDRA; KUMAR, SACHIN; TYAGI, BHAWANA; VERMA, MED RAM; KRISHNASWAMY, NARAYANAN (The Indian Journal of Animal Sciences, 2019)
In the present study, effect of dietary supplementation of fish oil during the non-breeding season on the reproductive performance of the goats was investigated. Experimental does were fed an isocaloric diet of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) rich fish (FO; n=12) or palm oil (PO; n=12) for 71 days. Periodical ovarian scanning for 21 days from the day of supplementation (day 0) confirmed acyclicity. Estrus induction was done by intra-vaginal progesterone (P4) sponge for 14 days from day 22 to 35 of supplementation. Dietary FO did not affect serum P4 throughout the period of supplementation. Ovarian scanning studies revealed that neither the number of surface follicles nor the diameter of largest surface follicle was significantly different between the groups at any point of supplementation. Similarly, the concentration of serum estradiol (E2) and P4 on the day of induced estrus was comparable between the groups. However, supplementation of FO decreased the PGFM significantly on day 16–18 post-estrus. In conclusion, supplementation of EPA and DHA rich FO for about 10 weeks inhibited the endometrial PGF2α production during the luteolytic window at induced estrus; however, it did not improve the ovarian function and fertility in the seasonally acyclic goat.